Catalytic hydrogenation products of aromatic and aliphatic dicarboxylic acids - Shinde, Sunil; Deshpande, Raj M. (Asian Journal of Chemistry, 2019)
Hydrogenation of aromatic dicarboxylic acids gave 100 % selectivity to respective cyclohexane dicarboxylic acid with 5 % Pd/C catalyst. 5 % Ru/C catalyst was observed to give over hydrogenation products at 493 K and at lower temperature (453 K) the selectivity for cyclohexane dicarboxylic acids was increased. Hydrogenation of phthalic acid with Ru-Sn/Al2O3 catalyst was observed to give phthalide instead of 1,2-benzene dimethanol or 2-hydroxy methyl benzoic acid. Ru-Sn/Al2O3 catalyst selectively hydrogenated the carboxylic group of cyclohexane dicarboxylic acids to give cyclohexane dimethanol. Use of proper catalysts and reaction conditions resulted in desired products.